Mediating Effect of Green Maintenance Funds on The Relationship Between Facilities Management Challenges and Performance of NITDA Nigeria - Babayo, Musa Mustapha; Milala, Sani Inusa (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
This study examines the relationship between facilities management challenges, green maintenance funds, and organizational performance, focusing on the mediating role of green maintenance funds. As sustainability becomes a key focus in facilities management, challenges such as resource constraints, inadequate training, and lack of strategic planning hinder the effective implementation of green initiatives. Using a quantitative approach, the study collected survey data from facilities managers across various sectors and applied structural equation modeling (SEM) to analyze the relationships between the key variables. Results indicate that facilities management challenges significantly impact the allocation of green maintenance funds (? = 0.852, p = 0.000), which in turn positively influences performance (? = 0.190, p = 0.046). Furthermore, green maintenance funds partially mediate the relationship between management challenges and performance (? = 0.162, p = 0.000). These findings suggest that addressing management challenges by allocating green maintenance funds can enhance organizational performance. The study highlights the importance of investing in green maintenance practices to improve both environmental outcomes and overall efficiency. It recommends that organizations prioritize sustainability, overcome facilities management challenges, and allocate sufficient resources to green maintenance to improve performance.